2015
DOI: 10.1159/000440834
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Pulse Treatment of Graves' Ophthalmopathy Is Not Associated with Secondary Adrenocortical Insufficiency

Abstract: Objective: Graves' ophthalmopathy (GO) is an inflammatory disease in the orbital region. The first-line medical treatment is glucocorticoids. An important potential side effect of glucocorticoid treatment is suppression of the hypothalamic-pituitary-adrenal (HPA) axis with impairment of endogenous cortisol production, implicating symptoms of adrenocortical insufficiency, especially in the period after cessation of therapy with possible risks in cases of intercurrent illness. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…Data about the influence of intravenous glucocorticoids used in the treatment of GO on the HPA-axis are scarce. Greek and Danish studies showed no association between ivGCS treatment and AI development [9,10]. In our study the same conclusion was drawn.…”
Section: Discussionsupporting
confidence: 89%
“…Data about the influence of intravenous glucocorticoids used in the treatment of GO on the HPA-axis are scarce. Greek and Danish studies showed no association between ivGCS treatment and AI development [9,10]. In our study the same conclusion was drawn.…”
Section: Discussionsupporting
confidence: 89%
“…It is essential to strongly recommend following general measures of social confinement and distancing, hands and surfaces hygiene, shielding if and when going outside. Although intravenous glucocorticoid therapy for GO does not seem to be associated with secondary adrenal insufficiency [16], patients who recently finished the intravenous glucocorticoid treatment, and more obviously, those who completed a long-term course of oral glucocorticoids for GO, should be considered at risk of potentially having an acute adrenal crisis if they get infected by Coronavirus. Accordingly, they should receive instructions on how to recognize symptoms of incipient adrenal insufficiency, inform immediately their family doctor, and adjust the daily dose of hydrocortisone as indicated for sick days.…”
Section: Management Of Graves' Orbitopathy In Time Of Covid-19mentioning
confidence: 99%
“…In our research, we did not find a statistically significant decrease of serum and salivary cortisol before administration of the 12th IVMP pulse in comparison to evaluation before treatment, while one study showed a statistically significant decrease of serum cortisol concentration before administration of the 12th IVMP pulse [ 11 ]. The results of our study show that none of the patients developed secondary AI at the cessation of IVMP treatment in a cumulative dose of 4.5 g. Previous studies did not prove secondary AI after therapy with standard EUGOGO protocol (cumulative dose of 4.5 g IVMP) as well [ 11 , 12 , 13 ]. However, dynamic testing with synthetic ACTH has low sensitivity in ruling out secondary AI, especially when considering short-lasting (less than 4–6 weeks) AI [ 14 ].…”
Section: Discussionmentioning
confidence: 40%